Arts Impact on the Culture of People - Sharma, Mandakini (International Journal of Control and Automation, 2018)
The arts are commonly used in cultural studies because of their ability to disclose a culture's history, ideology, and customs. But when and how are young readers encouraged to reflect on the arts' place in society as a whole? This paper presents research into the ways in which children's books, in addition to being an independent art form, can provide narratives in which the arts are central to the individual's formative experiences and help shape their sense of self. The research presented here focuses on a collection of 12 children's picture books in which the protagonists are either passionate about the arts, or have a problem in life that may be solved by turning to the arts. A critical content examination of these publications, viewed through the prism of New Historicism and bolstered by social semiotics, exposes their potential for potent, authentic investigations into the importance of the arts in one's personal culture.